Editorial (Czech Journal of International Relations, 1992)
Dear Readers,we apologize that you did not receive the tfi numbers of our last year International relations magazine. This situation occurred because the completely new leadership of the Institute of International Affairs relations, which today is headed by an important world-renowned political scientist, professor dr. ing. Jifí Valenta (member of the prestigious organization Council on Foreign Relations, for many years also worked for the US Department of the Navy and today works as the director of the Institute for the Study of the Soviet Union and Eastern Europe and a professor of political science at the University of Miami's School of International Affairs, adviser Minister of Foreign Affairs CSFR), decided not to follow up onprevious editions of this magazine.